CUE CARD AS MEDIA FOR TEACHING SPEAKING - Rika Irawati (ICoTE Proceedings)
The objective of the research is to investigate how significant the improvement of students’ speaking skill is by using cue card as media for teaching speaking of third semester Accounting students of Pontianak State Polytechnic in the academic year of 2017/2018. The research methodology applied is pre-experimental study. The techniques of data collecting are pre-test and post-test of speaking. The development of students’ speaking can be seen from the interval score of pre-test and post-test. The interval significance is known by applying T-test. The result of data analysis shows that: (1) Pre-test mean score (6.22) is lower than post-test (7.69). The interval score of pre-test and post-test is 1.47; (2) t-obtained (16.3) is higher than t-table (2.045). It indicates the Alternative hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected. It can be concluded that the development of students’ speaking skill by using cue card is significant.